(untitled) (Journal of the College of Education for Women, 2019)
AbstructThis recearch is about studying the novel (doorstep’s women) by the Iraqinarrator Hadia Hussian, and I choose Semiolog as a Curriculum for thiscritical approach, because I think that this Semiotic curriculum has the abilityto read the Subjects and the narrative constructions. Which form the structureof the novel starting from the little to the characters.The focus is on many narrative constructions in the novel we havestudied the semiology of the tittle, the semiology of the cover, of the color, thenames of the characters and the semiology of the female characters.First the focus of the novel is on the women’s characters because mostof it’s characters are women. Secondly because these characters aresenestive and soft in expressing the Iraqian reality due to the three wars thatIraq has come through. Finally because the novelist constrates her intrest onthe female character. Intentionally to show the suffering of women due to theconstant wars that Iraq has come through.